A flexible self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery, and a preparation method and application thereof

CN122978618APending Publication Date: 2026-10-27BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611277172.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]为此,本发明的目的在于提供一种宽力学监测范围、可高弹回复的柔性自支撑聚合物压电薄膜及其制备方法和应用,解决了现有柔性多孔压电薄膜灵敏度低、泡孔结构易塌陷、回弹性差、制备工艺复杂且依赖高压极化后处理等问题

Benefits of technology

[0038]1.本发明提供了一种宽力学监测范围、可高弹回复的柔性自支撑聚合物压电薄膜及其制备方法和应用。所述薄膜的核心突破与积极进步效果在于:通过非溶剂相转化工艺构建出"球孔分级复合形貌"结构,将分段式线性力电检测范围扩展至约290kPa(200 N),同时在0~57kPa和57~290kPa两个区间内分别实现84mV/kPa和12mV/kPa的较高压电灵敏度,有效克服了现有技术中宽压力监测范围与高灵敏度难以兼顾的共性难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978618A_ABST
    Figure CN122978618A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of wide mechanical monitoring range, flexible self-supporting polymer piezoelectric film with high elastic recovery and its preparation method and application, belong to functional piezoelectric composite material and flexible wearable electronic sensing technical field.The present application constructs "ball hole hierarchical composite morphology" with micro / nano bubble and bubble skeleton inlaying microsphere by a controllable non-solvent phase inversion method.The composite structure not only overcomes the inherent defects such as the limited response range of traditional single porous structure, easy to collapse, but also effectively increases polarization site by its internal micro / nano level bubble network skeleton and supporting microsphere, and significantly improves piezoelectric sensitivity by using stress concentration and strain amplification effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of functional piezoelectric composite materials and flexible wearable electronic sensing technology, specifically to a flexible self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery, a method for preparing the same, and the application of the piezoelectric film in wearable piezoelectric generators and gait monitoring. Background Technology

[0002] Piezoelectric nanogenerators (PENGs) can directly convert mechanical energy (such as human movement, vibration, and pressure) in the environment into electrical energy through the piezoelectric effect, while also possessing pressure sensing capabilities. They hold broad application prospects in wearable energy harvesting, human motion rehabilitation, and health monitoring. With the rapid development of flexible wearable electronic devices, portable health monitoring systems, and IoT technology, application scenarios are placing higher demands on the comprehensive performance of PENGs, including electromechanical conversion efficiency, sensitivity, lightweight design, flexibility, and resilience. Especially in applications involving large loads, wide pressure range monitoring requires piezoelectric materials to possess both a sufficiently high upper limit for electromechanical sensing and good resilience and self-support after being subjected to high pressure loads to ensure sensor performance and structural stability.

[0003] Taking foot health and gait monitoring as an example, gait monitoring technology can convert daily walking activities into quantifiable physiological parameters, which has important clinical value in the early screening of neurological diseases such as Parkinson's disease, orthopedic rehabilitation assessment, and fall prevention in the elderly. However, current mainstream solutions rely on large-scale three-dimensional motion capture systems and professional data analysis, which are costly and complex to operate, making them difficult to promote and apply in home and community settings. Physiological studies have shown that plantar pressure can reach about 300 kPa during normal standing or walking, and can even exceed 350 kPa under special conditions; while the characteristic signals of key symptoms such as gait freezing and dragging are often concentrated in the low-pressure range below 50 kPa. Therefore, an ideal piezoelectric sensor must have sufficient sensitivity in the low-pressure range to capture weak gait characteristics, while maintaining a stable and linear mechanoelectric response over a wide pressure range to prevent sensor distortion. However, the upper limit of the mechanoelectric monitoring range of most existing piezoelectric composite materials is usually limited to within 200 kPa, and the signal tends to saturate beyond this threshold. While a few materials can still respond under higher pressures, their sensitivity drops significantly to less than 50 mV / kPa, making it difficult to effectively distinguish different stress levels. Furthermore, commercially available dense PVDF films not only suffer from excessively high modulus and insufficient compressibility, affecting foot comfort, but their piezoelectric constant, after high-voltage polarization, is only 20–25 pC / N, limiting their spatial resolution. Meanwhile, gait monitoring involves cyclic compression, bending, and shearing, placing comprehensive demands on materials' resilience, bending resistance, fatigue resistance, and thinness for a snug fit. These performance shortcomings, combined, make existing piezoelectric material systems ill-suited for the practical application requirements of foot gait monitoring.

[0004] To improve the flexibility and resilience of piezoelectric matrices while simultaneously ensuring piezoelectric response, current research typically involves blending polymer / piezoelectric ceramic composites with elastomers such as polyurethane (PU) and polydimethylsiloxane (PDMS) for modification. The elastomer component enhances the flexibility and deformability of the composite, aiming to broaden the upper limit of the piezoelectric response and optimize piezoelectric output. However, simple blending of PVDF with elastomers like TPU results in poor compatibility between the two phases, and the upper limit of ceramic filler filling and dispersion uniformity are limited, making it difficult to simultaneously improve piezoelectric conversion efficiency. Therefore, in recent years, researchers have increasingly turned to introducing micro / nanostructures into polymer piezoelectric composite systems as an alternative modification strategy to improve PENG sensitivity and monitoring range. Among these, porous structures can effectively reduce the elastic modulus of the material and enhance the piezoelectric response through local stress / strain amplification effects; simultaneously, the cellular network framework can provide buffering for impact loads, helping to broaden the piezoelectric monitoring range. However, traditional porous thin film fabrication processes (such as vapor phase foaming, template etching, high-temperature cryogenic casting, and 3D printing) generally suffer from cumbersome steps, high costs, and difficulty in large-scale production. Furthermore, post-forming processes typically require additional high-pressure polarization treatment, significantly increasing process complexity and severely hindering their widespread application. A more prominent concern is that existing porous thin films often exhibit a single-cell structure, which is prone to pore wall collapse and fatigue cracking under long-term cyclic compression loads. This results in insufficient self-support when integrated into high-pressure applications such as smart insoles, potentially leading to device failure. Moreover, as the porous structure gradually compacts during repeated compression, piezoelectric sensitivity decreases sharply, leading to unstable sensing performance and difficulty in maintaining stable, linear piezoelectric output over a wide mechanical range.

[0005] In summary, wearable sensing applications such as gait monitoring, operating under high pressure and repetitive use conditions, place comprehensive demands on the electromechanical monitoring range, piezoelectric sensitivity, flexibility, resilience, and self-support of polymer piezoelectric materials. Therefore, there is an urgent need to develop a flexible polymer piezoelectric film that possesses these properties and is easy to fabricate. Summary of the Invention

[0006] Therefore, the purpose of this invention is to provide a flexible self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery, as well as its preparation method and application, which solves the problems of low sensitivity, easy collapse of pore structure, poor resilience, complex preparation process and dependence on high voltage polarization post-processing of existing flexible porous piezoelectric films.

[0007] To solve the above-mentioned technical problems, the present invention provides the following technical solution:

[0008] This invention provides a flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery. The piezoelectric film comprises a piezoelectric polymer, a polymer elastomer, and a piezoelectric nano-ceramic filler. The mass ratio of the three components is (1–5):(1–4):(1–3); preferably, the mass ratio is (1–3):(1–2):(1–2); more preferably, the mass ratio is (1.5–2.5):(1.5–2):(1–2).

[0009] In one possible implementation, the piezoelectric polymer is selected from any one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-trifluoroethylene copolymer P (VDF-TrFE), or polyvinylidene fluoride-hexafluoropropylene copolymer P (VDF-HFP).

[0010] In one possible implementation, the polymer elastomer is preferably a polyurethane-based elastic polymer, selected from any one or more combinations of polyester thermoplastic polyurethane (TPU) or polyether TPU; wherein the soft segment of polyester TPU is polyester polyol, and the soft segment of polyether TPU is polyether polyol.

[0011] In one possible implementation, the piezoelectric nanoceramic filler is selected from any one or more combinations of lead zirconate titanate (PZT), barium titanate (BaTiO3), lead titanate (PbTiO3), or zinc oxide (ZnO); the particle size distribution of the piezoelectric nanoceramic filler is 100–1000 nm.

[0012] In one possible implementation, the piezoelectric film has a "spherical-pore hierarchical composite morphology" structure with micro / nano-scale pores and microspheres embedded in the pore framework; the pore network size is 5-50 μm, and the microsphere size is 5-25 μm, which is adjustable; preferably, the pore network framework size is 10-25 μm, and the microsphere size is 10-20 μm; more preferably, the pore size can be further refined to the nanometer level (<1 μm).

[0013] In one possible implementation, the piezoelectric film has a piezoelectric coefficient greater than 8 pC / N without the need for high-voltage polarization post-treatment, and the piezoelectric coefficient is adjustable, reaching a maximum of 42.6 pC / N; the open-circuit voltage of the piezoelectric film reaches 70V or more; the piezoelectric film maintains a piecewise linear mechanoelectric response in the range of approximately 290 kPa (200 N), with linear intervals of 0–57 kPa and 57–290 kPa, and piezoelectric sensitivities of 84 mV / kPa and 12 mV / kPa, respectively, within the above intervals.

[0014] In one possible implementation, the piezoelectric film simultaneously possesses good flexibility, self-support, and resilience. After repeated compression and folding, and with the stress released, the piezoelectric film can spring back on its own, and its surface is free of creases or stress streaks. The elastic modulus of the piezoelectric film is 0.01–0.5 MPa, the tensile strength is 1–5 MPa, and the elongation at break is 80%–320%. Preferably, the elastic modulus is 0.1–0.3 MPa, the tensile strength is 3.8–4.9 MPa, and the elongation at break is 280%–320%. The piezoelectric film withstands 10 cycles of dynamic cyclic impact. 4 It retains good resilience and shape even after repeated use.

[0015] In one possible implementation, the piezoelectric film has a porosity of 50% or more under the condition of one-time molding and no post-processing; preferably, the porosity is 70% to 75%.

[0016] In one possible implementation, the piezoelectric film has a low dielectric constant, <7; preferably, the dielectric constant is 3.5 to 4.

[0017] Secondly, this invention also provides a method for preparing the aforementioned flexible self-supporting polymer piezoelectric film. The preparation method employs a non-solvent phase inversion method (NIPS), utilizing bidirectional diffusion between solvent and non-solvent to form micropores in the polymer's depleted phase region. In the rich phase regions of the polymer elastomer and the piezoelectric polymer, respectively, a cell network framework and a microsphere structure are formed. The size of the cells and microspheres can be controlled by adjusting parameters such as the type and ratio of polymer, the type of coagulation bath, the molding temperature, the molding time, and the mold thickness. The specific preparation steps are as follows:

[0018] S1. The piezoelectric polymer and the polymer elastomer are mixed in a common good solvent and mechanically stirred to fully dissolve them to obtain a first mixed solution; the piezoelectric polymer is selected from any one or more combinations of polyvinylidene fluoride (PVDF), vinylidene fluoride-trifluoroethylene copolymer P (VDF-TrFE), or vinylidene fluoride-hexafluoropropylene copolymer P (VDF-HFP); the polymer elastomer is selected from any one or more combinations of polyester-type TPU or polyether-type TPU.

[0019] S2. The piezoelectric nano-ceramic filler is surface modified using a coupling agent to form a functional group encapsulation layer on the filler surface to improve its dispersibility and interfacial bonding in the polymer matrix, thereby obtaining a modified piezoelectric nano-ceramic filler, which is then ground to refine its particle size; the piezoelectric nano-ceramic filler is selected from any one or more combinations of lead zirconate titanate (PZT), barium titanate (BaTiO3), lead titanate (PbTiO3), or zinc oxide (ZnO).

[0020] S3. The modified piezoelectric nano-ceramic filler obtained in step S2 is added in batches to the first mixed solution in step S1 under continuous mechanical stirring, and the mixture is dispersed evenly to obtain the second mixed solution.

[0021] S4. Add small molecules containing isocyanate groups to the mixed solution obtained in step S3 and stir quickly until homogeneous; the small molecules containing isocyanate groups react with water to generate gas during the subsequent non-solvent phase transformation process, which promotes foaming and increases porosity.

[0022] S5. The mixed solution obtained in step S4 is poured into a mold, the mold is immersed in a non-solvent coagulation bath, and after being formed by non-solvent phase inversion, it is dried to obtain the flexible self-supporting polymer piezoelectric film.

[0023] In one possible implementation, the common good solvent in step S1 is selected from any one or a combination of strongly polar solvents such as dimethylformamide (DMF), dimethylacetamide, N-methylpyrrolidone (NMP), or dimethyl sulfoxide (DMSO); the mass-to-volume ratio of the total mass of the piezoelectric polymer and the polymer elastomer to the good solvent is 100–300 mg / mL; the dissolution temperature is 25–80°C; and the dissolution time is 2–6 hours.

[0024] In one possible implementation, the coupling agent in step S2 is selected from one of the coupling agents such as silane coupling agents, titanate coupling agents, or organochromium complexes, preferably a silane coupling agent; the silane coupling agent is selected from any one or more combinations of KH-550, KH-560, or KH-570; the mass ratio of the silane coupling agent to the piezoelectric nano-ceramic filler is 1:(30-100); the solvent in the surface modification process is any one or more combinations of hydrolysis solvents such as water, ethanol, methanol, or isopropanol; the mass ratio of the piezoelectric nano-ceramic filler to the solvent is 1:(1-5); the modification temperature is 20-40℃; and the modification time is 8-12 hours.

[0025] In one possible implementation, the mass-to-volume ratio of the modified piezoelectric nanoceramic filler to the piezoelectric polymer solution obtained in step S1 is 5–30 mg / mL; the stirring speed is 200–1000 rpm; the blending temperature is 25–40 °C; and the blending time is 1–2 hours.

[0026] In one possible implementation, the small molecule containing isocyanate groups in step S4 is selected from any one or more combinations of small molecules containing isocyanate groups such as isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), or toluene diisocyanate (TDI); the mass-to-volume ratio of the small molecule containing isocyanate groups to the solvent is 1 to 10 mg / mL.

[0027] In one possible implementation, the non-solvent coagulation bath in step S5 is a poor solvent for the piezoelectric polymer and polymer elastomer, selected from any one or more combinations of water, methanol, ethanol, octanol, or ethyl acetate; preferably, the non-solvent coagulation bath is water or a mixture of ethanol and water (volume ratio of 1:1 to 3); the mold thickness is 100 μm to 1 mm; the volume of the non-solvent coagulation bath is 0.5 to 3 L; the molding temperature is 0 to 40 °C; the molding time is 0.5 to 12 hours; the drying temperature is 30 to 80 °C; the drying time is 4 to 12 hours; and the mold thickness for casting the modified piezoelectric nano-ceramic filler / piezoelectric polymer solution is 100 μm to 1 mm.

[0028] Thirdly, the present invention provides the application of the above-mentioned flexible self-supporting polymer piezoelectric film in the fields of wearable piezoelectric generators and gait monitoring.

[0029] The flexible self-supporting polymer piezoelectric film is cut into rectangular sheets. Low-resistance conductive layers are applied as electrodes to the upper and lower surfaces of the piezoelectric film, respectively. The conductive layers are selected from copper foil, aluminum foil, conductive double-sided adhesive, or conductive silver paste, preferably copper foil. Wires are led out from the outside of the electrode layers. The wires are selected from DuPont wires, copper wires, or flexible flat cables, and are electrically connected to the electrode layers by conductive adhesive or self-adhesion. An insulating encapsulation layer is used to encapsulate the device as a whole. The encapsulation layer is selected from polyimide (PI) tape, nano-transparent tape, or polydimethylsiloxane (PDMS) film, preferably PI tape. After encapsulation, a flexible self-supporting piezoelectric generator is obtained.

[0030] The flexible self-supporting piezoelectric generator is attached to the joints, soles of the feet, or the surface of wearable clothing and equipment. Through human movement (such as walking, running, flexing and extending the wrist, etc.), the device undergoes periodic deformation, generating piezoelectric output. After being rectified by a rectifier circuit, it charges energy storage elements (such as capacitors and lithium batteries), thereby realizing self-powered power supply for low-power wearable electronic devices.

[0031] Based on the skeletal structure of the human foot and the physiological distribution characteristics of foot pressure, multiple encapsulated piezoelectric sensing units are arranged in sections and integrated into the insole base material to form a smart piezoelectric sensing insole.

[0032] In one specific embodiment, the piezoelectric sensing unit uses the above-mentioned flexible self-supporting polymer piezoelectric film. After cutting, electrode application, wire lead-out and insulating encapsulation, a standardized sensing unit is obtained with a size of (1~5)cm×(1~3)cm.

[0033] In a preferred embodiment, the thickness of the copper foil is 0.01–0.1 mm, the encapsulation thickness of the PI tape is 0.02–0.1 mm, and the overall thickness of the device is 0.2–2 mm.

[0034] In a preferred embodiment, the insole is divided into a toe area, a forefoot area (including the area from the first to the fifth metatarsal bones), an arch area, and a heel area according to the characteristics of foot pressure distribution. Each area is arranged with a corresponding number of piezoelectric sensing units, totaling 10 to 20 sensing units, preferably 15. The sensing units are flatly attached to the surface of the insole base material and fixed by adhesive or double-sided tape. Each sensing unit is independent and does not interfere with each other.

[0035] In one possible implementation, the insole base material is selected from EVA foam, polyurethane foam, silicone or rubber, and has a thickness of 3 to 10 mm.

[0036] After the piezoelectric signals collected by the above sensing units are integrated by a multi-channel data acquisition system, the plantar voltage distribution map and plantar pressure distribution map are generated by signal processing algorithms (including signal amplification, filtering, analog-to-digital conversion and normalization). By analyzing the characteristic parameters of plantar pressure distribution, the functions of gait abnormality warning, trembling rise and Parkinson's disease gait freeze feature capture are realized.

[0037] The technical solution of the present invention achieves the following beneficial technical effects:

[0038] 1. This invention provides a flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery, as well as its preparation method and applications. The core breakthrough and positive progress of the film lies in the following: a "spherical-pore hierarchical composite morphology" structure is constructed through a solvent-free phase transformation process, extending the segmented linear mechanical and electrical detection range to approximately 290 kPa (200 N). Simultaneously, high piezoelectric sensitivities of 84 mV / kPa and 12 mV / kPa are achieved in the 0–57 kPa and 57–290 kPa ranges, respectively, effectively overcoming the common challenge in existing technologies of balancing a wide pressure monitoring range with high sensitivity.

[0039] The aforementioned performance breakthroughs are attributed to the triple synergistic enhancement effect of the "spherical-pore hierarchical composite morphology": First, the microspheres, embedded within the pore network framework, act as stress concentration points under stress, generating a local strain amplification effect. This allows the piezoelectric polymer to produce a large electrical displacement output under relatively low external forces, thereby achieving a high-sensitivity response in the low-pressure range. Second, the microspheres provide structural support to the pore network framework: on the one hand, they improve the compressibility of the material, enabling the film to withstand higher pressure loads without densification and compaction, thus broadening the upper limit of the electromechanical response; on the other hand, they effectively suppress pore wall collapse and fatigue cracks in single-pore structures under cyclic compression, enhancing fatigue resistance. Third, the hierarchical composite morphology of the pore network and embedded microspheres allows the film to maintain a low elastic modulus while possessing sufficient structural stiffness, endowing the film with good self-support and resilience. This ensures that the device can still rebound after repeated stress without surface creases or stress creasing, providing structural protection for stable electromechanical response over a wide pressure range. Based on the above structural design principles, the piezoelectric thin film possesses high porosity (preferably >68%), high β-phase content (approximately 70%), and low dielectric constant (preferably <4). Under relatively low forces, the quasi-static piezoelectric coefficient d 33 Up to 42.6 pC / N; with increasing load, the open-circuit voltage can exceed 70V, and the maximum power density reaches 110 μW·cm. -3 After 10 4 After several dynamic shock cycles, the electrical output and morphological integrity remained stable, demonstrating good long-term cyclic stability and ensuring the signal accuracy and reliability of the sensor across the entire measurement range.

[0040] 2. Utilizing the piezoelectric properties and comprehensive mechanical properties of the aforementioned piezoelectric film, on the one hand, the flexible self-supporting polymer piezoelectric sensor can be attached to human joints, soles of the feet, or the surface of wearable clothing and equipment. It generates piezoelectric output through human movement, which, after rectification, charges the energy storage element, enabling self-powering of low-power wearable electronic devices. On the other hand, the intelligent insole sensor array, integrated with 15 sensing units, can monitor the pressure distribution on the sole of the foot in real time, thereby achieving gait pattern recognition and gait freezing and early fall warning for Parkinson's disease patients. Furthermore, based on the structural design of a "spherical-pore hierarchical composite morphology," the piezoelectric film can simultaneously improve the electromechanical monitoring range and sensitivity under conditions of directional stretching, high-temperature sintering, or high-pressure polarization post-treatment, balancing the sensing requirements of wide range and high sensitivity. Moreover, the fabrication process is simple and low-cost, making it suitable for large-scale production and widespread application in home settings. Attached Figure Description

[0041] Figure 1 A schematic diagram of the flexible self-supporting polymer piezoelectric thin film sensor in this invention;

[0042] Figure 2A physical image of the flexible self-supporting polymer piezoelectric thin film sensor of this invention;

[0043] Figure 3 The torsional and bending properties of the flexible self-supporting polymer piezoelectric film in this invention are shown in the photograph.

[0044] Figure 4 Photographs illustrating the self-supporting resilience of the flexible self-supporting polymer piezoelectric film in this invention;

[0045] Figure 5 The elemental distribution diagram of the microsphere positions in the flexible self-supporting polymer piezoelectric film of this invention;

[0046] Figure 6 This is a diagram showing the distribution of the pore network framework elements in the flexible self-supporting polymer piezoelectric film of the present invention.

[0047] Figure 7 Infrared spectrum of a flexible self-supporting polymer piezoelectric film with a spherical-pore hierarchical composite morphology;

[0048] Figure 8 Microscopic images of the spherical aperture hierarchical composite morphology of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, 5, and 6;

[0049] Figure 9 Porosity of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5;

[0050] Figure 10 Dielectric constants of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5;

[0051] Figure 11 Stress-strain curves of the flexible self-supporting polymer piezoelectric films prepared in Examples 1-5;

[0052] Figure 12 DSC curve of the flexible self-supporting polymer piezoelectric film prepared in Example 1;

[0053] Figure 13 The quasi-static piezoelectric coefficients (d) of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5 33 );

[0054] Figure 14 Electrical properties of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5 under conditions of 50 N and 1 Hz;

[0055] Figure 15 A comparison of the piezoelectric performance of the flexible self-supporting polymer piezoelectric thin film sensor in Example 4 and the commercial solid PVDF piezoelectric sensor in Comparative Example 1 in the range of 1–200 N.

[0056] Figure 16 Output power (50N, 1Hz) of the flexible self-supporting polymer piezoelectric thin film sensor in Example 4 under different external resistors.

[0057] Figure 17 The flexible self-supporting polymer piezoelectric thin film sensor of Example 4 was tested at 10... 4 Piezoelectric output stability under one dynamic compression cycle (50N, 1Hz);

[0058] Figure 18 The charging curves of the flexible self-supporting polymer piezoelectric film sensor of Example 4 attached to different outdoor equipment for charging a 10 μF capacitor: (a) trekking pole tip; (b) trekking pole handle; (c) backpack strap; (d) charging curve of the enlarged device driven by foot pedaling.

[0059] Figure 19 The flexible self-supporting polymer piezoelectric thin film sensor of Example 4 was used to identify voltage distribution cloud maps and fit pressure distribution cloud maps of foot posture: (a) normal foot posture; (b) eversion; (c) inversion;

[0060] Figure 20 The flexible self-supporting polymer piezoelectric film sensor of Example 4 is used to identify voltage distribution cloud maps and fitted pressure distribution cloud maps of gait characteristics of Parkinson's disease patients: (a) Schematic diagram of a Parkinson's patient in a trembling standing state; (b) Foot voltage signal in the standing state; (c) Foot fitted pressure signal in the standing state; (d) Schematic diagram of a gait frozen state; (e) Foot voltage signal in the gait frozen state; (f) Foot fitted pressure signal in the gait frozen state. Detailed Implementation

[0061] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0062] The technical solution of the present invention will be further described below with reference to specific embodiments. All reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing; the instruments used in the embodiments are commercially available.

[0063] Example 1

[0064] This embodiment provides a flexible self-supporting polymer piezoelectric film, which is prepared by the following method:

[0065] S1. Take P(VDF-TrFE) and polyether-type TPU at a mass ratio of 1:1, add them to DMF / DMAc solvent, the solid content is 200mg / mL, stir and dissolve at 50℃ for 4 hours to obtain the first mixed solution;

[0066] S2. Dissolve 0.8g of KH-550 silane coupling agent in 80mL of ethanol / water mixed solvent (volume ratio 8:2), and stir magnetically for 10min at 25℃ to obtain coupling agent solution; add 56g of PZT nano-ceramic powder, stir and react at 35℃ for 12 hours, and obtain modified piezoelectric nano-ceramic filler after drying and grinding.

[0067] S3. The modified PZT obtained in step S2 is added in batches to the piezoelectric polymer solution in step S1 under continuous mechanical stirring, so that the mass ratio of P(VDF-TrFE):TPU:PZT is 1:1:1. The mixture is stirred at 40°C for 1.5 hours to disperse it evenly, and a second mixed solution is obtained.

[0068] S4. Add IPDI to the mixed solution obtained in step S3 to make its concentration 5 mg / mL, and stir quickly until homogeneous to obtain a third mixed solution that can self-foam.

[0069] S5. The third mixed solution obtained in step S4 is poured into a 200μm thick mold, immersed in a 1 L pure water coagulation bath, and molded at 25°C for 2 hours. After being removed, it is dried at 50°C for 8 hours to obtain a white flexible self-supporting polymer piezoelectric film.

[0070] Example 2

[0071] This embodiment provides a flexible self-supporting polymer piezoelectric film, which is prepared by the following method:

[0072] S1. Take PVDF and polyether-type TPU at a mass ratio of 2.5:3, add them to a DMAc / NMP mixed solvent with a solid content of 250 mg / mL, stir and dissolve at 60°C for 5 hours to obtain the first mixed solution;

[0073] S2. Dissolve 0.5g of KH-560 silane coupling agent in 80mL of ethanol / water mixed solvent (volume ratio 9:1), and stir magnetically at 30℃ for 20min to obtain coupling agent solution; add 40g of ZnO nano-ceramic powder, stir and react at 40℃ for 12 hours, and obtain modified piezoelectric nano-ceramic filler after drying and grinding.

[0074] S3. The modified ZnO obtained in step S2 is added in batches to the piezoelectric polymer solution in step S1 under continuous mechanical stirring, so that the mass ratio of PVDF:TPU:ZnO is 2.5:3:1. The mixture is stirred at 40°C for 1.5 hours to disperse it evenly, and a second mixed solution is obtained.

[0075] S4. Add MDI to the mixed solution obtained in step S3 to make its concentration 6.5 mg / mL, and stir quickly until homogeneous to obtain a third mixed solution that can self-foam.

[0076] S5. The third mixed solution obtained in step S4 is poured into a 300μm thick mold, immersed in a 1.5L ethanol / water coagulation bath (volume ratio 8:2), and molded at 15℃ for 4 hours. After being removed, it is dried at 55℃ for 7 hours to obtain a white flexible self-supporting polymer piezoelectric film.

[0077] Example 3

[0078] This embodiment provides a flexible self-supporting polymer piezoelectric film, which is prepared by the following method:

[0079] S1. Take P(VDF-HFP) and polyester TPU at a mass ratio of 1.5:2 and add them to NMP / DMSO mixed solvent. The solid content is 175 mg / mL. Stir and dissolve at 55℃ for 6 hours to obtain the first mixed solution.

[0080] S2. Dissolve 0.7g of KH-570 silane coupling agent in 80mL of methanol / water mixed solvent (volume ratio 7:3), and stir magnetically at 30℃ for 30min to obtain coupling agent solution; add 45g of BaTiO3 nano-ceramic powder, stir and react at 35℃ for 10 hours, and obtain modified piezoelectric nano-ceramic filler after drying and grinding.

[0081] S3. The modified BaTiO3 obtained in step S2 is added in batches to the piezoelectric polymer solution in step S1 under continuous mechanical stirring, so that the mass ratio of P(VDF-HFP):TPU:BaTiO3 is 1.5:2:1. The mixture is stirred at 30°C for 1.5 hours to disperse it evenly, thus obtaining the second mixed solution.

[0082] S4. Add TDI to the mixed solution obtained in step S3 to make its concentration 8 mg / mL, and stir quickly until homogeneous to obtain a third mixed solution that can self-foam.

[0083] S5. The third mixed solution obtained in step S4 is poured into a 500μm thick mold, immersed in a 1.5L water / methanol coagulation bath (volume ratio 8:2), and molded at 5℃ for 4 hours. After being removed, it is dried at 60℃ for 4 hours to obtain a white flexible self-supporting polymer piezoelectric film.

[0084] Example 4

[0085] This embodiment provides a flexible self-supporting polymer piezoelectric film, which is prepared by the following method:

[0086] S1. Take P(VDF-TrFE) and polyester TPU at a mass ratio of 1:1.5 and mix them together. Add the mixture to a DMF / DMSO mixed solvent with a solid content of 225 mg / mL. Stir and dissolve the mixture at 45°C for 6 hours to obtain the first mixed solution.

[0087] S2. Dissolve 0.5g of KH-550 silane coupling agent in 80mL of methanol / water mixed solvent (volume ratio 9:1) and stir magnetically at 25℃ for 30min to obtain coupling agent solution; add 50g of PZT nano-ceramic powder and stir at 30℃ for 10 hours. After drying and grinding, obtain modified piezoelectric nano-ceramic filler.

[0088] S3. The modified PZT obtained in step S2 is added in batches to the piezoelectric polymer solution in step S1 under continuous mechanical stirring, so that the mass ratio of P(VDF-TrFE):TPU:PZT is 1:1.5:0.8. The mixture is stirred at 40°C for 2 hours to disperse it evenly, thus obtaining the second mixed solution.

[0089] S4. Add IPDI to the mixed solution obtained in step S3 to make its concentration 3 mg / mL, and stir quickly until homogeneous to obtain a third mixed solution that can self-foam.

[0090] S5. The third mixed solution obtained in step S4 is poured into a 400μm thick mold, immersed in a 1 L pure water coagulation bath, and molded at 0℃ for 4 hours. After being taken out, it is dried at 50℃ for 4 hours to obtain a white flexible self-supporting polymer piezoelectric film.

[0091] Example 5

[0092] This embodiment provides a flexible self-supporting polymer piezoelectric film, which is prepared by the following method:

[0093] S1. Take P(VDF-TrFE) and polyether-type TPU at a mass ratio of 1:2 and add them to a DMF / DMAc mixed solvent (volume ratio of 8:2). The solid content is 225 mg / mL. Stir and dissolve at 50°C for 5 hours to obtain the first mixed solution.

[0094] S2. Dissolve 0.5g of KH-560 silane coupling agent in 100mL of isopropanol / water mixed solvent (volume ratio 8:2), and stir magnetically at 30℃ for 30min to obtain coupling agent solution; add 45g of PZT nano-ceramic powder, stir and react at 30℃ for 8 hours, and obtain modified piezoelectric nano-ceramic filler after drying and grinding.

[0095] S3. The modified PZT obtained in step S2 is added in batches to the piezoelectric polymer solution in step S1 under continuous mechanical stirring, so that the mass ratio of P(VDF-TrFE):TPU:PZT is 1:2:1. The mixture is stirred at 30°C for 2 hours to disperse it evenly, thus obtaining the second mixed solution.

[0096] S4. Add IPDI to the mixed solution obtained in step S3 to make its concentration 10 mg / mL, and stir quickly until homogeneous to obtain a third mixed solution that can self-foam.

[0097] S5. The third mixed solution obtained in step S4 is poured into a 500μm thick mold, immersed in a 2L water / isopropanol coagulation bath (volume ratio 7:3), and molded at 0℃ for 3 hours. After being removed, it is dried at 60℃ for 4 hours to obtain a white flexible self-supporting polymer piezoelectric film.

[0098] Example 6

[0099] This embodiment provides a flexible self-supporting polymer piezoelectric film, which is prepared by the following method:

[0100] S1. Take P(VDF-TrFE) and polyester TPU at a mass ratio of 1:1, add them to DMF mixed solvent (volume ratio 6:4), the solid content is 205mg / mL, stir and dissolve at 50℃ for 5 hours to obtain the first mixed solution.

[0101] S2. Dissolve 0.4g of KH-550 silane coupling agent in 100mL of ethanol / water mixed solvent (volume ratio 7:3), and stir magnetically at 30℃ for 30min to obtain coupling agent solution; add 50g of PZT nano-ceramic powder, stir and react at 30℃ for 8 hours, and obtain modified piezoelectric nano-ceramic filler after drying and grinding.

[0102] S3. The modified PZT obtained in step S2 is added in batches to the piezoelectric polymer solution in step S1 under continuous mechanical stirring, so that the mass ratio of P(VDF-TrFE):TPU:PZT is 1:2:1. The mixture is stirred at 30°C for 2 hours to disperse it evenly, thus obtaining the second mixed solution.

[0103] S4. The second mixed solution obtained in step S3 is poured into a 300μm thick mold, immersed in a 1L water / isopropanol coagulation bath (volume ratio 7:3), and molded at 0℃ for 3 hours. After being removed, it is dried at 60℃ for 4 hours to obtain a white flexible self-supporting polymer piezoelectric film.

[0104] Example 7

[0105] This embodiment provides a piezoelectric generator based on a flexible self-supporting polymer piezoelectric film and its application in electromechanical conversion in wearable devices. The specific fabrication process is as follows:

[0106] S1. Take the P(VDF-TrFE) / polyester TPU / PZT flexible self-supporting polymer piezoelectric film prepared in Example 4 and cut it into a rectangular sheet of 3.5cm×2cm.

[0107] S2. Apply 0.03mm thick copper foil to the upper and lower surfaces of the film as conductive electrode layers. Lead out copper wires from the outer sides of the electrode layers at both ends and connect them to the electrode layers through conductive silver paste. Use 0.05mm thick PI tape to encapsulate the device as a whole, so that the tape extends 2mm beyond the edge of the device, to obtain a flexible self-supporting piezoelectric generator.

[0108] S3. Record the open-circuit voltage with an oscilloscope. Under an impact pressure of about 200N (about 290kPa), the peak-to-peak value of the output voltage is measured to be over 70V. After passing through a full-wave rectifier circuit, it is connected to 3.3μF and 4.7μF capacitors respectively. The voltage across the capacitors can be charged to 20V within 70s and 130s.

[0109] S4. The piezoelectric generator was attached to the surface of outdoor hiking poles, backpacks and shoes to collect mechanical energy. It was observed that the charge accumulation rate changed systematically with different types of exercise, which verified the device's ability to collect and convert mechanical energy of human movement.

[0110] Example 8

[0111] This embodiment provides a smart insole based on a flexible self-supporting polymer piezoelectric film, demonstrating its application in monitoring foot posture and gait pressure. The specific fabrication process is as follows:

[0112] S1. Take 15 pieces of P(VDF-TrFE) / polyester TPU / PZT flexible self-supporting polymer piezoelectric film prepared in Example 4, cut each piece into a standardized sensing unit of 3.5cm×2cm, attach copper foil electrodes and lead out wires, and encapsulate with PI tape.

[0113] S2. Based on the pressure distribution characteristics of the human foot, 15 sensor units are arranged in sections on the surface of the EVA foam insole base (5 mm thick): 3 in the toe area, 4 in the forefoot area (1 in the first metatarsal area and 3 in the second to fifth metatarsal areas), 4 in the arch area, and 4 in the heel area, for a total of 15 units. They are fixed with double-sided tape, and each unit maintains an independent spacing and completely covers the sole area. The wires of each sensor unit are connected to a multi-channel data acquisition system.

[0114] S3. When the subject wears the smart insole and walks in a normal posture, with the foot inward and outward, the piezoelectric signals at the positions of 15 sensing units are tested respectively. The plantar voltage distribution for different foot postures is obtained by fitting. Then, based on the wide range of electromechanical response relationship of the piezoelectric film of the present invention, the pressure distribution of the plantar surface is fitted and constructed.

[0115] S4. In the simulated trembling rise and gait freezing dragging walking tests of Parkinson's disease patients: during the rise, the pressure at the patient's heel increased significantly, indicating that Parkinson's patients have a tendency to lean backward; during the gait freezing process, the piezoelectric signals on the sole of the foot were relatively dispersed and the signal amplitude decreased, reflecting the patient's slow and dragging walking characteristics. The above results verify the system's ability to identify gait abnormalities, indicating that the present invention has application value in gait health monitoring and early fall warning in home settings.

[0116] Comparative Example 1

[0117] This comparative example provides a piezoelectric generator based on a commercially available solid PVDF film, and the preparation method is as follows:

[0118] S1. Cut commercial solid PVDF film into rectangular sheets of 3.5cm × 2cm.

[0119] S2. Apply 0.03mm thick copper foil to the upper and lower surfaces of the film as conductive electrode layers. Lead out copper wires from the outer sides of the electrode layers at both ends and connect them to the electrode layers through conductive silver paste. Use 0.05mm thick PI tape to encapsulate the device as a whole, so that the tape extends 2mm beyond the edge of the device, to obtain a commercial PVDF piezoelectric generator.

[0120] S3. The commercial PVDF piezoelectric generator was subjected to performance testing under the same test conditions as in Example 6. The results showed that the commercial solid PVDF film had an open-circuit voltage of only 15V, a pressure monitoring upper limit of less than 70kPa, and obvious creases appeared on the surface after folding, failing to spring back on its own. In contrast, the flexible self-supporting polymer piezoelectric film prepared in Example 4 was significantly superior to the commercial PVDF film in terms of open-circuit voltage, monitoring range, resilience, and cycle stability.

[0121] The following tests were performed on the flexible self-made piezoelectric films and their sensors prepared in Examples 1-8 and Comparative Example 1, as well as on the piezoelectric sensor based on a commercially available PVDF film.

[0122] β-phase content determination:

[0123] The β-phase content within the piezoelectric thin film was determined using a Fourier transform infrared reflectance spectrometer (FT-IR, Nicolet 6700). The scanning range was 4000–400 cm⁻¹. -1 The resolution is 4cm.-1 The number of scans was 32. By analyzing the changes in the peak position and peak area of ​​the characteristic absorption peaks, based on 840 cm⁻¹... -1 and 764cm -1 The intensity ratio of the absorption peak at the given point is used to calculate the relative content of the β phase. The content of the β phase in the piezoelectric active phase (F) is also considered. β ) is calculated using the following formula:

[0124] ;

[0125] Where A α and A β The α and β phases of PVDF are respectively located at 768 cm⁻¹. -1 and 840cm -1 absorbance at K α and K β The absorption coefficients are 6.1 × 10⁻⁶. 4 and 7.7×10 4 cm 2 ·mol -1 .

[0126] Microscopic morphological observation:

[0127] The dispersion of the modified piezoelectric nanoceramic filler and the growth of the "spherical-pore hierarchical composite morphology" were observed using a scanning electron microscope (SEM, TESCAN VEGA3). Before testing, the samples were fractured in liquid nitrogen and then subjected to gold sputtering treatment (sputtering current of 10 mA for 60 s), with an accelerating voltage of 10 kV and a magnification of 200–30000 times.

[0128] Tensile mechanical property testing:

[0129] The tensile mechanical properties of the materials were tested using a universal tensile testing machine (CTM2050, Shanghai Xieqiang Manufacturing Co., Ltd.). Samples were cut into dumbbell shapes (effective size 20mm × 4mm), the tensile rate was 50mm / min, and the gauge length was 20mm. At least five parallel samples were tested for each sample, and the average value was recorded. The elongation at break, modulus of elasticity, and tensile strength were also recorded.

[0130] Piezoelectric output performance test:

[0131] The electromechanical response testing platform was built in-house. A stepper motor (LXCXPT-BH, Beijing Feichuangyi Technology Co., Ltd.) was fixed on a standardized optical testing platform (OTS18-12, Beijing Feichuangyi Technology Co., Ltd.) as a dynamic pressure application device, with a stroke range of 0–20 mm and an adjustable speed (1–25 mm / s). A piezoelectric device was placed on the surface of a mechanical sensor (DS2-XD, Guangdong Zhiqu Precision Technology Co., Ltd.) to test the dynamic pressure value on the device surface. The piezoelectric output signal of the device was measured using an electronic electrometer (Keithley 6517B), and the following electrical parameters were recorded: open-circuit voltage (Voc), short-circuit current (Isc), transferred charge (Q), and output power (P) calculated through an external resistor. The test frequency was 0.5–5 Hz, and the applied pressure was 1–200 N.

[0132] Quasi-static piezoelectric constant (d 33 )test:

[0133] Using quasi-static d 33 The piezoelectric constant of the material was measured using a testing instrument (ZJ-3AN, Institute of Acoustics, Chinese Academy of Sciences). The test frequency was 110 Hz, and the preload was 0.2 N. In the experiment, the piezoelectric material was cut into square samples with sides of approximately 0.5–1 cm and clamped in the center of the probe for testing.

[0134] Thermal properties and system compatibility characterization:

[0135] The melting point and system compatibility of the materials were characterized using a differential scanning calorimeter (DSC, Netzsch DSC 214). Tests were conducted under a nitrogen atmosphere, with a temperature range of 0–200 °C and a heating rate of 10 °C / min. -1 Record the melting peak temperature (T) of the sample. m The compatibility of the components in the system can be determined by the presence of a single melting peak or the presence of multiple peaks.

[0136] Elemental distribution and composition analysis:

[0137] Energy dispersive spectroscopy (EDS, JSM-IT510 scanning electron microscope, JEOL) was used to perform elemental surface distribution and point scanning analysis to analyze the elemental distribution and semi-quantitative composition of the pore network framework, microspheres and modified piezoelectric nanoceramic fillers in the flexible self-supporting polymer piezoelectric film, so as to analyze the formation mechanism of "spherical-pore hierarchical composite morphology" and evaluate the dispersion uniformity of fillers in the polymer matrix.

[0138] Porosity test:

[0139] The porosity of the piezoelectric elastomer was determined using the water displacement method. The sample was vacuum dried at 60°C to constant weight, and the dry weight (W0) was recorded. The sample was then completely immersed in ethanol for 24 hours, and after removal, the surface moisture was gently absorbed with filter paper, and the wet weight (W1) was recorded. Porosity (ε, %) was calculated using the following formula:

[0140] Porosity(%)=(W1-W0) / ρV;

[0141] Where W1 is the weight of the sample after soaking in ethanol for 24 hours until saturation (removing residual liquid from the surface), W0 is the initial weight of the dried sample, ρ is the density of ethanol, and V is the volume of the sample.

[0142] In this invention, the prepared sensor structure is as follows: Figure 1 As shown, the actual object is as follows Figure 2 As shown.

[0143] The torsional and bending properties of the flexible self-supporting polymer piezoelectric film prepared in Example 1 were tested, such as... Figure 3 As shown, the self-supporting resilience of the flexible self-supporting polymer piezoelectric film prepared in Example 1 is as follows: Figure 4 As shown. By Figure 4 It can be seen that, under the synergistic effect of the polymer elastomer TPU and the spherical hierarchical composite morphology, the flexible self-supporting polymer piezoelectric film can be twisted, folded, and bent at will. Furthermore, after stress release, the flexible self-supporting polymer piezoelectric film automatically returns to its initial state, with no creases or stress streaks on the surface, indicating that the flexible self-supporting polymer piezoelectric film possesses good flexibility and resilience. When the size is 5cm × 5cm, the piezoelectric film has a mass of 0.32g, a thickness of 220μm, and a density of approximately 0.58g / cm³. 3 This further demonstrates the lightweight and ultrathin characteristics of the piezoelectric film.

[0144] Elemental analysis was performed on the flexible self-supporting polymer piezoelectric film prepared in Example 1, wherein the elemental distribution of the microsphere positions is as follows: Figure 5 As shown, the distribution of positional elements in the pore network skeleton is as follows: Figure 6 As shown, Figure 5 and Figure 6 It can be used to explain the formation mechanism of the composite morphology of microspheres and pore network skeleton in flexible self-supporting polymer piezoelectric films. Figure 5 In the diagram, blue represents the region where the microsphere morphology is formed (Spc1-5). According to the given element intensity distribution diagram, N element is almost undetectable, O element content is low, specifically about 7.04-8.21 wt%, while F element content is 31.17-36.11 wt%. The proportion of F element is much higher than that of N and O elements, indicating that the microsphere morphology here is mainly formed by the solidification of P(VDF-TrFE) rich phase. Figure 6In the diagram, green represents the regions where the cell network framework is formed (Spc6-8). At this point, the C element content is slightly reduced, and N element is detected in all regions, with the highest content being 5.2 wt%. However, the F element content drops below 10.96 wt%, and even below 5 wt% in Spc6 and Spc8, indicating that this region primarily consists of a cell network framework morphology formed by the rich phase curing of TPU. The specific element content percentages are summarized in Table 1.

[0145] Table 1. Local elemental content at the pore network framework and microsphere morphology of P(VDF-TrFE) / TPU / PZT flexible self-supporting polymer piezoelectric films with "spherical hierarchical composite morphology".

[0146]

[0147] The aforementioned elemental distribution characteristics validate the mechanisms by which the P(VDF-TrFE)-rich and TPU-rich phase regions form microspheres and cell network frameworks, respectively. Furthermore, after modification with KH-550, the surface hydroxyl groups (-OH) of PZT undergo dehydration condensation with the silanol groups (Si-OH) of KH-550, exposing the amino groups (-NH2) at the other end of KH-550 to the outside, making it easier to form hydrogen bonds with the urethane groups (-NHCOO-) in the TPU molecular chain. Therefore, the contents of Pb and Ti in the cell network framework are significantly higher than those in the microspheres, verifying that the modified PZT filler tends to disperse within the TPU phase, thereby forming strong interfacial hydrogen bonds with the cell network framework and achieving good dispersion.

[0148] The infrared spectra of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5 are shown below. Figure 7 As shown in the figure, the horizontal axis represents wavenumber, and the vertical axis represents relative absorbance. The figure displays the characteristic absorption peaks of the α and β phases. Calculations show that the β-phase content in the three systems of Examples 1, 4, and 5 is approximately 63%, 66%, and 51%, respectively. The β-phase content in Example 4 reaches 66%, comparable to the level of PVDF films treated with high-pressure polarization, indicating that during the solvent-free phase conversion molding process, the solidification shrinkage of the microspheres and the stretching of the cellular network framework are beneficial to the formation of the β-phase. Furthermore, by adjusting factors such as the type and ratio of polymers, the type of coagulation bath, the molding temperature, and the molding time during the piezoelectric film preparation process, the piezoelectric phase content within the system can be effectively adjusted, thereby achieving the purpose of regulating piezoelectric properties.

[0149] SEM images of the microstructure of piezoelectric films prepared by using P(VDF-TrFE) with different types of TPU at different mass ratios are shown below. Figure 8As shown, the scale bars are 100, 20, and 10 μm respectively. Due to the intrinsic differences in solubility parameters (especially the hydrogen bonding component δH) and hydrophilicity between P(VDF-TrFE) copolymer and TPU, they exhibit different nucleation and growth kinetics during NIPS phase separation. Taking Example 1 as an example, since the proportion of P(VDF-TrFE) is the highest, the proportion of microspheres is greater and their size is larger. Therefore, different morphologies can be prepared by controlling factors such as the type and proportion of polymers in the flexible self-supporting polymer piezoelectric film system, the type of coagulation bath, molding temperature, and molding time. Specifically, the cell network and microsphere diameter are distributed in the range of 5–50 μm and 5–25 μm, respectively. Thus, the morphology of the system can be flexibly controlled according to the requirements of resilience and mechanical properties for different application scenarios.

[0150] The porosity of the flexible self-supporting polymer piezoelectric films in Examples 1, 4, and 5 is as follows: Figure 9 As shown. By Figure 9 As can be seen, the porosity gradually increases as the proportion of the polymer elastomer TPU in the examples increases, i.e., as the ratio of P(VDF-TrFE):TPU increases from 1:1 to 1:2. This is because the two polymers have different molding mechanisms. TPU molecular chains have a large number of hydrophilic groups, such as ether bonds (-O-), ester groups (-COO-), and amide groups (-CONH-). Therefore, TPU molecules are bound by water molecules at the moment of phase transformation, thus forming an elastic cell network framework in situ. In Example 5, the porosity is as high as approximately 68.4%. When the proportion of P(VDF-TrFE) is larger, a microsphere structure with a larger volume ratio is formed. This is also because PVDF copolymers exhibit strong hydrophobicity (usually water contact angle > 90°), so the molecular chains shrink into microspheres at the moment of contact with water. Therefore, by adjusting the ratio of the two in the system, different porosities and different morphological combinations can be achieved to meet the needs of different application scenarios.

[0151] The dielectric constants of the flexible self-supporting polymer piezoelectric films in Examples 1, 4, and 5 are as follows: Figure 10 As shown in the figure, the horizontal axis represents frequency, and the vertical axis represents dielectric constant. The test frequency range is 0–8 MHz. The figure shows that introducing TPU with a low dielectric constant and an air-rich multi-scale pore network with micropores reduces the dielectric constant, and the reduction is positively correlated with porosity. When the porosity of Example 5 reaches 68%, the dielectric constant is generally distributed in the range of 3.5–4. According to the piezoelectric equation, the piezoelectric voltage constant (g...) 33 The dielectric constant of the piezoelectric ceramic powder decreases as the dielectric constant increases, thus offsetting the high dielectric constant of the piezoelectric ceramic powder. Therefore, the design of this flexible self-supporting polymer piezoelectric film is structurally advantageous for improving piezoelectric output.

[0152] The stress-strain curves of the flexible self-supporting polymer piezoelectric films in Examples 1-5 are as follows: Figure 11 As shown in the figure, the horizontal axis represents tensile strain, and the vertical axis represents tensile stress. (From...) Figure 11 As can be seen, in Example 1, the proportion of P(VDF-TrFE) is the highest, resulting in the highest mechanical strength (6.5 MPa) but a lower elongation at break (70%) for the piezoelectric film. However, by optimizing the ratio of these two components and the synergistic optimization of the phase transformation process conditions, a comprehensive optimization of both mechanical strength and elongation at break can be achieved. In Example 5, the mechanical strength and elongation at break are 5.1 MPa and 290%, respectively. Therefore, the mechanical properties of the flexible self-supporting polymer piezoelectric film of this invention are related to the ratio of the cellular network and the microspheres, and their mechanical properties can be flexibly adjusted to meet the needs of different application scenarios.

[0153] The DSC curve of the flexible self-supporting polymer piezoelectric film prepared in Example 1 is as follows: Figure 12 As shown in the figure, the horizontal axis represents temperature, and the vertical axis represents heat flow. The figure shows that the melting point range of the system is 131℃ to 155℃, demonstrating that the system possesses sufficient thermal stability for use in various wearable devices that come into contact with the human body. Furthermore, the system exhibits only one stable main melting peak, demonstrating the good compatibility of the flexible self-supporting polymer piezoelectric film system, and revealing a clear melting peak splitting phenomenon due to the composite morphology within the system.

[0154] The quasi-static piezoelectric coefficient (d) of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5 33 )like Figure 13 As shown. Without any post-polarization treatment, the piezoelectric elastomer films all exhibited good piezoelectric properties, and the overall system's d... 33 Widely distributed in the range of several to tens, or even hundreds of pC / N, with a maximum d 33 It can exceed 42 pC / N. Its piezoelectric coefficient is influenced by both the type and amount of piezoelectric polymer in the system, and the internal composite microstructure. Taking Example 1 as an example, although the proportion of piezoelectric polymer P(VDF-TrFE) is the highest, and the proportion and volume of piezoelectric microspheres are the largest, its d... 33 Approximately 15.2 pC / N. However, this did not reach the maximum value, indicating that the piezoelectric coefficient of the piezoelectric film is not simply positively correlated with the content of the piezoelectric material. In Example 4, d 33The piezoelectric coefficient increased significantly from 15.2 pC / N to 42.6 pC / N, demonstrating the significant effect of the "spherical-pore hierarchical composite morphology" introduced in this invention on improving the piezoelectric coefficient. At this point, the increase in porosity and the synergistic oscillatory polarization of the microsphere morphology jointly promoted the increase in piezoelectric coefficient. The advanced composite structure obtained through a simple process in this invention allows for flexible adjustment of the piezoelectric coefficient of the piezoelectric film, avoiding the negative impacts of traditional complex post-processing on material cost and stability.

[0155] The electrical properties of the flexible self-supporting polymer piezoelectric films prepared in Examples 1, 4, and 5 at 50 N and 1 Hz are as follows: Figure 14 As shown in the figure, the horizontal axis represents time, and the vertical axis represents the open-circuit voltage (a) and output charge (b) across the piezoelectric device, respectively. The figure shows that in Example 4, when the mass ratio of P(VDF-TrFE):TPU:PZT is 1:1.5:0.8, the IPDI concentration is 3 mg / mL, the coagulation bath is a 1L DMF / H2O coagulation bath (volume ratio 9:1), and DMF is used as the solvent with a solid content of 250 mg / mL, the piezoelectric film exhibits the strongest output. Furthermore, the piezoelectric output is related to… Figure 10 Chinese material d 33 The consistent trend demonstrates the effectiveness of the "spherical aperture hierarchical composite morphology" structure in enhancing the piezoelectric output of polymer piezoelectric films. Under preferred conditions, the open-circuit voltage and transferred charge can reach 42V and 30nC, respectively, significantly superior to the commercial PVDF film in Example 7 and the piezoelectric film materials in the background art.

[0156] The piezoelectric performance comparison graph of the flexible self-supporting polymer piezoelectric thin film sensor in Example 4 and the commercial solid PVDF piezoelectric sensor in Comparative Example 1 in the range of 1–200 N is shown in the figure below. Figure 15 As shown. By Figure 15As can be seen, the flexible self-supporting polymer piezoelectric film sensor of Example 4 exhibits a piecewise linear response: in the range of 1–40 N (approximately 0–57 kPa), the piezoelectric sensitivity is approximately 84 mV / kPa; in the range of 40–200 N (approximately 57–290 kPa), the piezoelectric sensitivity is 12 mV / kPa. The open-circuit voltage and transferred charge maintain a linear relationship with the load in both ranges (R² > 0.99). When the load increases to 200 N, the maximum open-circuit voltage reaches 73 V, the transferred charge reaches 15 nC, and the piezoelectric output still shows a further increasing trend. In contrast, the commercial solid PVDF piezoelectric sensor of Comparative Example 1 reaches its voltage output peak at 50 N, and the voltage signal no longer increases with further increases in load; the transferred charge reaches its peak at 100 N. These results demonstrate that the flexible self-supporting polymer piezoelectric film sensor of the present invention simultaneously possesses high piezoelectric output, piezoelectric sensitivity, and a wide force-electric sensing range. This performance advantage stems from the novel "spherical aperture hierarchical composite morphology" structural design, which can achieve high piezoelectric output and wide-range electromechanical response without post-processing or high-voltage polarization, far exceeding commercial PVDF films.

[0157] Example 4: Output power of the flexible self-supporting polymer piezoelectric thin film sensor under different external resistance conditions, such as... Figure 16 As shown in the figure, the horizontal axis represents the resistance range (0–100 MΩ), and the vertical axis represents voltage, current, and power, respectively. The figure shows that as the external resistance increases, the voltage across it gradually increases from 1V to 23V. According to Ohm's law, the current gradually decreases during this process, from 0.8 μA to 0.2 μA. Using U=I... 2 Calculations show that the power output reaches its maximum of approximately 7 μW with an external resistance of 40 MΩ. This piezoelectric power output successfully increases from the nanowatt level of typical PENGs to the microwatt level, thereby enabling the flexible self-supporting polymer piezoelectric film sensor of this invention to have high-efficiency power conversion capabilities in wearable devices.

[0158] The piezoelectric output stability of the flexible self-supporting polymer piezoelectric thin film sensor in Example 4 under 10,000 dynamic compression cycles (50N, 1Hz) is as follows: Figure 17 As shown in the figure, the horizontal axis represents the cycle time, and the vertical axis represents the output voltage. The figure shows that the output voltage hardly decreases with increasing cycle number, indicating that the cell network framework, supported by the intercalated microspheres, has good self-support and resilience, enhancing the film's resistance to permanent deformation and thus maintaining the stability of the piezoelectric output.

[0159] The charging curves of the flexible self-supporting polymer piezoelectric film sensor of Example 4, attached to different outdoor equipment, and the charging of a 10μF capacitor are shown below. Figure 18As shown in the figure, the horizontal axis represents time, and the vertical axis represents charge. The figure shows that when the sensor is attached to the tip and handle of a trekking pole, it charges the capacitor to 200 μC within approximately 500 s and 300 s, respectively. Subsequently, when the sensor is attached to the backpack strap, it exhibits different charging rates under different movement conditions (walking or running), indicating that the sensor has high sensitivity to external force loads. When the device area is enlarged to 11 cm × 12.5 cm and attached to the sole of the foot, it can accumulate 200 μC of total charge within 60 s under high pressure. The results indicate that, under passive force conditions, the charging rate of this piezoelectric film can meet the energy conversion needs of most everyday sports scenarios.

[0160] Example 4 uses a flexible self-supporting polymer piezoelectric thin film sensor to identify the plantar voltage distribution cloud map and fitted pressure distribution cloud map when identifying foot posture, as shown in the example. Figure 19 As shown. Figure 19 As shown in (a), during normal walking posture, plantar pressure is mainly distributed in the first metatarsal region, the first phalanx region, the lateral arch, and the center of the heel, with a relatively uniform pressure distribution across these areas. This indicates that in a healthy state, pressure is distributed across the plantar surface according to the skeletal structure. However, in simulated foot eversion (…),… Figure 19 (b) or inversion of the foot ( Figure 19 (c) In this state, plantar pressure is often concentrated on one side, opposite to the direction of the affected foot's contact with the ground. The flexible self-supporting polymer piezoelectric film of the present invention has a wide mechanical monitoring range and high piezoelectric sensitivity, and can distinguish the plantar pressure distribution characteristics under different foot postures, providing a material system and structural design scheme for home-based portable foot posture diagnosis.

[0161] The plantar voltage and fitted pressure distribution cloud map of the foot posture recognition of Parkinson's disease patients using the flexible self-supporting polymer piezoelectric thin film sensor of Example 4 are shown below. Figure 20 As shown. Figure 20 (a) is a schematic diagram of a Parkinson's patient's trembling ascent. Figure 20 (b) It can be seen that in the stiff, trembling standing posture, the piezoelectric response area of ​​the anterior and middle regions of the sole is significantly reduced, especially the peak piezoelectric signal at the toes and first metatarsal bone. Specifically, the forces corresponding to the first and second metatarsal bones decrease to below 25.5 N and 16.5 N, respectively. Meanwhile, the high-pressure zone in the heel region significantly increases, with the peak force exceeding 60 N. Figure 20 (c) The above results indicate that patients tend to lean backward during the sitting-to-standing transition, reflecting a tendency for Parkinson's disease patients to fall backward during the trembling ascent, which can be life-threatening in severe cases.

[0162] Figure 20(e) shows the plantar voltage signal in a Parkinson's disease patient under gait freeze, compared to the normal gait. Figure 19 (a) The voltage levels decreased overall across all regions. Specifically, a maximum voltage of approximately 52 V was observed in the first metatarsal region, while values ​​in other regions were all below 42 V, and the pressure recognition across different locations on the sole of the foot was relatively dispersed. This phenomenon is associated with the gait dragging characteristics of Parkinson's disease patients, manifested as delayed push-off and shuffling steps. Figure 20 (f) shows that the maximum plantar force was approximately 58 N, a decrease of about 56% compared to the normal gait. This result is consistent with the weakened voluntary control of the plantar muscles, making the patient more prone to falls and mobility impairments.

[0163] In summary, the flexible self-supporting polymer piezoelectric film sensor of the present invention can track dynamic pressure changes on the sole of the foot during walking to reveal gait details, and predict the fall risk of Parkinson's disease patients by detecting abnormalities in pressure values ​​and spatial distribution. It has good application prospects in the fields of elderly health monitoring and intelligent rehabilitation.

[0164] It is obvious that the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of the claims of this patent application.

Claims

1. A flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery, characterized in that, The flexible self-supporting polymer piezoelectric film is made of piezoelectric polymer, polymer elastomer and modified piezoelectric nano-ceramic filler in a mass ratio of (1-5):(1-4):(1-3). The open-circuit voltage and mechanical load of the flexible self-supporting polymer piezoelectric film maintain a linear relationship in the 0-57 kPa range and the 57-290 kPa range, respectively. The piezoelectric sensitivity of the flexible self-supporting polymer piezoelectric film is 84 mV / kPa in the 0-57 kPa range and 12 mV / kPa in the 57-290 kPa range.

2. The flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery as described in claim 1, characterized in that, The flexible self-supporting polymer piezoelectric film has a spherical-pore hierarchical composite morphology structure with micro / nano-scale pores and microspheres embedded in the pore framework.

3. The flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery as described in claim 1, characterized in that, The pore size of the foam is 5–50 μm, and the particle size of the microspheres is 5–25 μm.

4. The flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery as described in claim 1, characterized in that, The piezoelectric polymer is any one or more of vinylidene fluoride and vinylidene fluoride copolymers, and the polymer elastomer is a polyurethane elastomer polymer.

5. The flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery as described in claim 1, characterized in that, The porosity of the flexible self-supporting polymer piezoelectric film is greater than or equal to 60%.

6. The method for preparing the flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery as described in claim 1, characterized in that, Includes the following steps: S1. Material preparation: Prepare piezoelectric polymer, polymer elastomer and modified piezoelectric nano-ceramic filler in a mass ratio of (1~5):(1~4):(1~3); S2. The piezoelectric polymer and the polymer elastomer are mixed in a common good solvent and mechanically stirred to fully dissolve them to obtain the first mixed solution. S3. Preparation of modified piezoelectric nano-ceramic fillers: The piezoelectric nano-ceramic fillers are obtained by surface modification and grinding using coupling agents. S4. The modified piezoelectric nano-ceramic filler obtained in step S3 is added to the first mixed solution obtained in step S2 under continuous mechanical stirring and dispersed evenly to obtain the second mixed solution. S5. The second mixed solution obtained in step S4 is poured into a mold, and then the mold is immersed in a non-solvent coagulation bath. The second mixed solution is solidified and shaped by non-solvent conversion. After drying, a flexible self-supporting polymer piezoelectric film can be obtained.

7. The preparation method according to claim 6, characterized in that, In step S2, the common good solvent is selected from any one or more of dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; the mass-to-volume ratio of the total mass of the piezoelectric polymer and the polymer elastomer to the common good solvent is 100–300 mg / mL; the temperature at which the piezoelectric polymer and the polymer elastomer are dissolved in the common good solvent is 25–80°C, and the dissolution time is 2–6 hours.

8. The preparation method according to claim 6, characterized in that, In step S3, the coupling agent is a silane coupling agent, a titanate coupling agent, or an organochromium complex; in step S5, the liquid used in the non-solvent coagulation bath is one or more of water, methanol, ethanol, octanol, and ethyl acetate.

9. The preparation method according to claim 6, characterized in that, In step S5, before pouring the second mixed solution obtained in step S4 into the mold, small molecules containing isocyanate groups are added to the second mixed solution and stirred evenly to obtain an improved second mixed solution. Then, the improved second mixed solution is poured into the mold, and the mold is then immersed in a non-solvent coagulation bath. The improved second mixed solution is solidified and formed by using a non-solvent conversion method. The small molecules containing isocyanate groups are one or more of isophorone diisocyanate, diphenylmethane diisocyanate, and toluene diisocyanate. The mass-volume ratio of the small molecules containing isocyanate groups to the common good solvent is 1 to 10 mg / mL.

10. The application of the flexible, self-supporting polymer piezoelectric film with a wide mechanical monitoring range and high elastic recovery as described in any one of claims 1 to 5, characterized in that, Used as a piezoelectric unit in the fields of wearable piezoelectric generators and gait monitoring.